PROJECT-BASED LEARNING: ANALISIS TERHADAP PERSPEKTIF BARAT DAN ISLAM SERTA RELEVANSI KEDUANYA DENGAN PEMBELAJARAN ERA SOCIETY 5.0 - Midi HS; Mahridawati; Lilik Aminah; Asniah (STIT Darul Hijrah Martapura, 2026)
The education of society 5.0 era requires learners not only to possess technological skills but also can think reflectively, innovatively, and collaboratively in responding to contemporary challenges. This study aims to examine Project-Based Learning (PjBL) from Western and Islamic perspectives and explore their relevance to Society 5.0 era learning to find a holistic perspective of the PjBL concept. The study employed using a qualitative approach and documentary research method by analyzing 33 documents related to PjBL from Western and Islamic perspectives and society 5.0 era learning. Data were collected through documentation and analyzed using Bowen’s procedures, which starts from skimming to conclusion. The results indicate that Western PjBL is grounded in Dewey’s pragmatism and progressivism, emphasizing real experiences, active learner participation, and social problem-solving, meanwhile from Islamic perspective, the PjBL concept is in line with the educational thoughts of Al-Attas, Al-Ghazali, and Khaldun, which emphasize the integration of knowledge, action, and moral values. Both perspectives are relevant to society 5.0 era learning, because they both emphasize active learning and are oriented towards solving real-world problems. Furthermore, when these two concepts are integrated, it is believed they can form a holistic learning model that can shape students into whole human beings.